Application of Genetic Algorithm in Optimizing LQR Control for Ball and Beam - Nguyen-Dang-Khoa Tran; Minh-Quan Nguyen; Tuan-Kiet Le; Duy-Khanh Bui; Thanh-Vinh Le; Thi-Ngoc-Thi Vo; Thi-Toi Nguyen; Ngo-Quoc-Bao Pham (Robotica & Management, 2023)
In this paper, we apply genetic algorithm (GA) to optimize LQR controller – a linear control algorithm which stability is guaranteed by mathematics. This searching algorithm proves its ability in finding better control parameters through generations. Our model is ball and beam (B&B) – a classical single input – multi output (SIMO) system. This system is balanced around equilibrium point in simulation.